Changes in benthic communities of the Minonosok Bight (Posyet Bay, Japan Sea) - Irina R. Levenets; Eugeny B. Lebedev (Известия ТИНРО, 2015)
Composition and structure of benthic communities in the Minonosok Bight (Posyet Bay, Japan Sea) are considered on the surveys data obtained in the 1990s and 2012. In total, 140 taxa of benthic organisms were found in the 1990s with domination of mollusks and algae by the species number, abundance; biomass, and occurrence; their total biomass was high, up to 29 kg/m2. All these parameters became lower in the 2012 when the monodominant communities changed mainly to polydominant ones. In the 2012, the macroalgae weren’t fasten onto the bottom in the southern part of the bay because of its silting, but they were attached to mussel druses. Trophic structure of the sublittoral communities was changed: the producers were replaced by sestonophages, detritophages and predators.